2013
DOI: 10.1507/endocrj.ej12-0277
|View full text |Cite
|
Sign up to set email alerts
|

Low-molecular-weight adiponectin is more closely associated with episodes of asthma than high-molecular-weight adiponectin

Abstract: Adiponectin plays various rolls in energy metabolism [1], lipid metabolism [2][3][4] and appestat regulation [5]. It has also attracted considerable attention regarding its anti-inflammatory activities, including inhibiting immune responses in macrophages [6,7]. Adiponectin activates AMP kinase, resulting in decreased NF-κb activity and decreased levels of CRP mRNA and proteins [8]. However, Schaffler et al. reported that increased adiponectin levels occur concomitantly with inflammatory responses [9]. They ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 29 publications
0
18
2
Order By: Relevance
“…The average duration of asthma and the percentage of subjects who received inhaled steroids among the asthmatic subjects were 16.7 ± 14.4 cantly associated with "current asthma." A previous report regarding the LMW adiponectin-asthma association demonstrated that the level of LMW adiponectin was significantly lower among subjects who had experienced episodes of asthma [35], and these results were different from our findings in that the levels of LMW adiponectin were significantly higher among the subjects with current asthma. This discrepancy may have been caused by the difference in study subjects (past asthma vs. current asthma).…”
Section: Clinical Characteristics Of Subjects In Groupcontrasting
confidence: 99%
See 4 more Smart Citations
“…The average duration of asthma and the percentage of subjects who received inhaled steroids among the asthmatic subjects were 16.7 ± 14.4 cantly associated with "current asthma." A previous report regarding the LMW adiponectin-asthma association demonstrated that the level of LMW adiponectin was significantly lower among subjects who had experienced episodes of asthma [35], and these results were different from our findings in that the levels of LMW adiponectin were significantly higher among the subjects with current asthma. This discrepancy may have been caused by the difference in study subjects (past asthma vs. current asthma).…”
Section: Clinical Characteristics Of Subjects In Groupcontrasting
confidence: 99%
“…This discrepancy may have been caused by the difference in study subjects (past asthma vs. current asthma). However, in the previous study [35], when they analyzed the multivariate regression analysis, they treated the LMW adiponectin level as a dependent variable and the presence or absence of asthma episodes as an independent variable, respectively, and showed that the regression coefficient was 0.098 (SE, 0.033; P = 0.004), suggesting that LMW adiponectin was positively correlated with a history of asthma episodes. In other words, we believe that their results show that LMW adiponectin was higher among subjects with a history of asthma episodes than among To date, although several reports have examined the correlation between asthma and serum adiponectin levels, these studies have measured only the total adiponectin level and have not investigated the association between asthma and the various isoforms of adiponectin (HMW, MMW and LMW) [7][8][9][10][11][12][13][14][15][16][17].…”
Section: Clinical Characteristics Of Subjects In Groupmentioning
confidence: 99%
See 3 more Smart Citations